2021
DOI: 10.2196/preprints.28771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Digital Health Interventions on Parents’ Mental Health Literacy and Help Seeking for Their Child’s Mental Health Problem: Systematic Review (Preprint)

Abstract: UNSTRUCTURED Introduction: Many children with a mental health problem do not receive professional help. Despite frequent use of digital health interventions (DHI) such as websites or online service navigation platforms for child mental health, their effects on parent’s mental health knowledge, help-seeking or uptake of professional services for their child are unclear. Methods: Systematic review and narrative synthesis to describe whether DHIs improve the above parental outcomes and whe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The attitudes of preschool children and infants were investigated very little, with only one study focusing on these age groups [36]. This result can be explained by the fact that there are very few DHIs designed for very young age groups [53]. For example, a scoping review published in 2019 on DHI and mental health literacy for the children aged 2 to 12 years children found only 4 results [53].…”
Section: Population Recruitment and Countries Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…The attitudes of preschool children and infants were investigated very little, with only one study focusing on these age groups [36]. This result can be explained by the fact that there are very few DHIs designed for very young age groups [53]. For example, a scoping review published in 2019 on DHI and mental health literacy for the children aged 2 to 12 years children found only 4 results [53].…”
Section: Population Recruitment and Countries Of Originmentioning
confidence: 99%
“…This result can be explained by the fact that there are very few DHIs designed for very young age groups [53]. For example, a scoping review published in 2019 on DHI and mental health literacy for the children aged 2 to 12 years children found only 4 results [53]. To the best of our knowledge, no previous review has explored the engagement of families of toddlers and preschool children in DHIs.…”
Section: Population Recruitment and Countries Of Originmentioning
confidence: 99%
“…In 2014, a systematic review of 18 studies of web-based interventions targeting help-seeking in young people aged between 14 and 25 years (only 4 of which included adolescents) found that although the trials did not change in help-seeking behavior, quasi-experimental and cross-sectional studies reported that interventions facilitated seeking professional help for an average of 35% of users [12]. A recent scoping review of 4 studies of digital health interventions aimed at improving help-seeking behavior or access to mental health services among parents or caregivers of 2-to 12-year-olds concluded there was some evidence of improved mental health literacy but not necessarily help-seeking [13].…”
Section: Introductionmentioning
confidence: 99%